Adaptive Chirp Transform for frequency measurement - Mostarac, Petar; Malarić, Roman; Hegeduš, Hrvoje (Measurement : journal of the International Measurement Confederation, 2012)
► In this paper new Adaptive Chirp Transform (ACT) is proposed for power frequency measurement. ► Results of analysis are showing that ACT has a significantly lower number of operations compared to classic CZT. ► ACT is very fast method which is able to determine frequency of non-stationary sinus signal. In this paper Adaptive Chirp Transform (ACT) algorithm for power frequency measurement is presented. It is adjusted for continuous monitoring of power frequency. Signal is first preprocessed with adaptive filter to minimize the error of non-linear model parameters. The resulting parameters are used to narrow the frequency range for CZT method to be effective. Algorithm code has been analyzed and computation complexity has been significantly decreased. Using this algorithm it is possible to measure frequency transients with sufficient accuracy and low execution time. Algorithm is verified through simulations and real-time data.